Children's cognitive reflection predicts successful interpretations of covariation data - Young, Andrew G.; Shtulman, Andrew (Frontiers in Developmental Psychology, 2024)
Cognitive reflection is the ability and disposition to reflect on one's own thinking, allowing a person to identify and correct judgments grounded in intuition rather than logic. Cognitive reflection strongly predicts school-aged children’s understanding of counterintuitive science concepts. Here, we asked whether children’s cognitive reflection similarly predicts a domain-general scientific skill: the interpretation of covariation data. Five- to 12-year-olds (N = 74) completed a children’s Cognitive Reflection Test (CRT-D) and measures of executive functioning. They also interpreted covariation data presented in 2 x 2 contingency tables. CRT-D performance predicted children’s overall accuracy and the strategies they used to evaluate the contingency tables, even after adjusting for their age, set-shifting ability, inhibitory control, and working memory. Thus, the relationship between cognitive reflection and statistical reasoning emerges early in development. These findings suggest cognitive reflection is broadly involved in children’s scientific thinking, supporting domain-general data-interpretation skills in addition to domain-specific conceptual knowledge.